ARE POTENTIALLY RESECTABLE COLORECTAL LIVER METASTASES SLIPPING THROUGH THE NET?. (8th June 2013) - Keville, N; Jones, C; McAfee, A; Ahmad, J; Dasari, B; McKie, L; Taylor, M A; Diamond, T
Abstract : Introduction: Liver is the most common site of metastatic spread in colorectal cancer, and its management has significantly evolved in recent decades with liver resection now being the optimal treatment. Aims/Background: This study aimed to assess referral patterns from colorectal multidisciplinary meetings (MDMs) throughout Northern Ireland to the Regional HPB Unit. Method: Over a 6 week period all colorectal MDMs throughout the five health and social care trusts were reviewed. Patients with colorectal liver metastases (CRLMs) were included in the study. The following data were included: patient demographics, details of the health and social care trust, date of MDM discussion, primary tumour pathology, and the MDM outcome. These findings were subsequently compared with regional guidelines for the referral of CRLMs to assess if the decision was deemed appropriate. Results: 21 discussions were recorded, which involved 20 patients, with a mean age of 69 years and 13 were male. 40% of patients were from the Belfast trust, while the remainder was evenly distributed between the 4 remaining trusts. All CRLMs discussed were confirmed by computerised tomography scanning, and the MDM decision was deemed to be appropriate in 85% of patients. Only 15% of patients had KRAS testing performed and 20% were subsequently referred for PET-CT scanning. Conclusion: The majority of potentially resectable colorectal liver metastases had an appropriate outcome in terms of management and referral to the Regional HPB unit. However, this could still be further streamlined through both education, and highlighting the role of PET-CT and KRAS testing.